Generation of human islet cell type-specific identity genesets - van Gurp, Léon; Fodoulian, Leon; Oropeza, Daniel; Furuyama, Kenichiro; Bru-Tari, Eva; Vu, Anh Nguyet; Kaddis, John S.; Rodríguez, Iván; Thorel, Fabrizio; Herrera, Pedro L. (Nature communications, 2022)
Generation of surrogate cells with stable functional identities is crucial for developing cell-based therapies. Efforts to produce insulin-secreting replacement cells to treat diabetes require reliable tools to assess islet cellular identity. Here, we conduct a thorough single-cell transcriptomics meta-analysis to identify robustly expressed markers used to build genesets describing the identity of human α-, β-, γ- and δ-cells. These genesets define islet cellular identities better than previously published genesets. We show their efficacy to outline cell identity changes and unravel some of their underlying genetic mechanisms, whether during embryonic pancreas development or in experimental setups aiming at developing glucose-responsive insulin-secreting cells, such as pluripotent stem-cell differentiation or in adult islet cell reprogramming protocols. These islet cell type-specific genesets represent valuable tools that accurately benchmark gain and loss in islet cell identity traits. Cell therapy to replace β-cells is a potential therapeutic avenue to treat diabetes, but the production of insulin-secreting replacement cells requires reliable tools to assess islet cellular identity. Here the authors use single-cell transcriptomics meta-analysis to construct gene sets that describe the identity of human α-, β-, γ- and δ-cells.